Knowledge needs in patients with Liver Disease: a qualitative study - Birgitte Gade Jacobsen; Mette Munk Lauridsen; Lea Ladegaard Grønkjaer (BMC, 2023)
Abstract Background Knowledge is essential for patients' disease management strategies and a critical component of healthcare. The importance of increasing patients level of knowledge has become more widely acknowledge in liver disease management in recent years, but further studies are needed to address patients experiences of unmet knowledge needs to develop appropriate patient education strategies. Therefore, the aim of this study was to explore knowledge needs in patients' with liver disease of different etiology and severity. Methods A qualitative study was designed and an inductive method was chosen. Thirty-three patients with liver disease of different etiology and severity were interviewed using a semi-structured interview guide. Content analysis was used as an inspiration to describe and compare patients' needs for knowledge across disease etiology and severity. The reporting followed consolidated criteria for reporting qualitative research. Results The analysis generated three categories and nine subcategories. In general, the patients described lack of knowledge related to their liver disease, which made it difficult for them to manage their disease. Patients wished to be more involved in care and treatment of the liver disease. However, patients' had difficulties to assess and understand the importance of the information they received from healthcare professionals. Due to lack of knowledge, patients' had a misconception of the liver disease. Patients' had variation in knowledge needs depending on liver disease etiology and severity. Conclusion Within liver disease management, knowledge of patients' experiences is vital to meet patients' knowledge needs and to develop appropriate patient education strategies. Therefore, it is important to ascertain a patient-centered approach to accommodate patients' individual knowledge needs, involve patients in care and treatment, and insure understanding to strengthen their self-management and give the patients the necessary skills to manage their disease and everyday life. Registration number Open Science Framework registration DOI https://doi.org/10.17605/OSF.IO/W28RC .